Answer:
500 g flour = 600 g
6*1.2 g salt = 7.2 g
12*1.2 g yeast = 14.4 g
30 mL oil = 36 mL
360 mL water = 432 mL
Step-by-step explanation:
10 bread rolls requires 500g of flour.
Eli uses 600g of flour which is 1.2 times the amount needed for 10 bread rolls.
This means that 1.2 * 10 bread rolls are made which is 12 bread rolls.
Multiply the remaining ingredients by 1.2:
500 g flour = 600 g
6*1.2 g salt = 7.2 g
12*1.2 g yeast = 14.4 g
30 mL oil = 36 mL
360 mL water = 432 mL
Answer:
this only goes to the thousanths.
Step-by-step explanation:
The first letter can be any one of 5. For each of those . . .
The second letter can be any one of the remaining 4. For each of those . . .
The third letter can be any one of the remaining 3. For each of those . . .
The fourth letter can be any one of the remaining 2. For either of those . . .
The fifth letter is the last remaining one.
Total number of possibilities = (5 x 4 x 3 x 2 x 1) =
<em> 120 ways</em> to line them up.
Now, may I say that being a hater of school is not something that
makes you cool. Maybe it does make you one of the crowd, but life
is not a war between you and school. School is simply something that
a lot of grown-ups spend a lot of money on, and a lot of teachers spend
their whole life on, to make sure that a lot of kids won't go through <em><u>their</u></em>
whole life stupid. You can learn everything you ever want to know there,
and it's all free. That's a pretty good deal.
Answer:
The value at x =3 is undefined for the given expression
Step-by-step explanation:
Given expression is ![\frac{2x^2+8x}{(x+4)(x^2-9)}](https://tex.z-dn.net/?f=%5Cfrac%7B2x%5E2%2B8x%7D%7B%28x%2B4%29%28x%5E2-9%29%7D)
To find for what value of x is undefined in the given expression :
![\frac{2x^2+8x}{(x+4)(x^2-9)}=\frac{2x(x+4)}{(x+4)(x^2-9)}](https://tex.z-dn.net/?f=%5Cfrac%7B2x%5E2%2B8x%7D%7B%28x%2B4%29%28x%5E2-9%29%7D%3D%5Cfrac%7B2x%28x%2B4%29%7D%7B%28x%2B4%29%28x%5E2-9%29%7D)
![=\frac{2x}{x^2-9}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B2x%7D%7Bx%5E2-9%7D)
![\frac{2x^2+8x}{(x+4)(x^2-9)}=\frac{2x}{x^2-9}](https://tex.z-dn.net/?f=%5Cfrac%7B2x%5E2%2B8x%7D%7B%28x%2B4%29%28x%5E2-9%29%7D%3D%5Cfrac%7B2x%7D%7Bx%5E2-9%7D)
If we put x=3 in the above expression we get
![\frac{2x}{x^2-9)}=\frac{2(3)}{3^2-9}](https://tex.z-dn.net/?f=%5Cfrac%7B2x%7D%7Bx%5E2-9%29%7D%3D%5Cfrac%7B2%283%29%7D%7B3%5E2-9%7D)
![=\frac{6}{9-9}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B6%7D%7B9-9%7D)
![=\frac{6}{0}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B6%7D%7B0%7D)
Therefore ![\frac{2x^2+8x}{(x+4)(x^2-9)}=\frac{6}{0}](https://tex.z-dn.net/?f=%5Cfrac%7B2x%5E2%2B8x%7D%7B%28x%2B4%29%28x%5E2-9%29%7D%3D%5Cfrac%7B6%7D%7B0%7D)
The value at x =3 is undefined for the given expression